Pressure Assisted Application of Tubular Nanofiber Forward Osmosis Membrane in Membrane Bioreactor Coupled with Reverse Osmosis System - Arslan, S.; Eyvaz, M.; Guclu, S.; Yuksekdag, A.; Koyuncu, I.; Yüksel, Ebubekir (Pleiades Publishing Ltd, 2021)
Membrane bioreactors (MBR) with osmotic pressure driven membranes have significant advantages over bioreactors operated with pressure driven membranes. Since no pressure is applied to the membrane, except the concentrate circulation, osmotic membranes are less prone to fouling. Membrane fouling is an important limiting factor in MBRs, resulting in a frequent plantservice and high operating costs. In addition, other issues such as concentrate management and increased demands for reuse of treated wastewater have led to research of new processes such as the use of osmotic membranes in MBRs. In this study, tubular electrospun nanofiber (TuEN) membrane was coated with polyamide layer (PA) and the tubular nanofiber forward osmosis (TuNFO) membrane was manufactured. It operated submerged in a laboratory scale MBR under application of vacuum and concentrate circulation at the same time. The output of MBR was a feed for the reverse osmosis (RO) system. The RO-concentrate recirculated along the submerged membrane. To achieve an increased water flux and low salt flux in the MBR, the vacuum pressure was applied to the submerged membrane by operating the vacuum pump. The MBR system operated for sixteen months without washing and cleaning, and relatively better water fluxes were obtained (averaged 7.35 L m(-2) h(-1)) compared to forward osmosis membrane bioreactors. The overall system (MBR + RO) exhibited high removal efficiencies for organic carbon (>99%), total nitrogen (TN) (70.8%), and total phosphorus (TP) (99.8%). With the concentrate management, the waste discharge of the entire system was minimized. The main point to be investigated more detailed in further studies is the relationship between the membrane structure and the operation mode. The pressure assisted circulation of saline concentrate without mixing with low concentrated feed through a membrane with suitable structure such as TuNFO membrane exhibits an important potential in MBR applications.
Keywords: tubular electrospun nanofiber (TuEN) membrane; tubular nanofiber forward osmosis (TuNFO) membrane; PA coating; forward osmosis (FO); vacuum concentrate circulation